Influence of species, size and relative abundance on the outcomes of competitive interactions between brook trout and juvenile coho salmon. Issue 2 (4th March 2017) - Thornton, Emily J.; Duda, Jeffrey J.; Quinn, Thomas P.
Abstract : Resource competition between animals is influenced by a number of factors including the species, size and relative abundance of competing individuals. Stream-dwelling animals often experience variably available food resources, and some employ territorial behaviors to increase their access to food. We investigated the factors that affect dominance between resident, non-native brook trout and recolonizing juvenile coho salmon in the Elwha River, WA, USA, to see if brook trout are likely to disrupt coho salmon recolonization via interference competition. During dyadic laboratory feeding trials, we hypothesized that fish size, not species, would determine which individuals consumed the most food items, and that species would have no effect. We found that species, not size, played a significant role in dominance; coho salmon won 95% of trials, even when only 52% the length of their brook trout competitors. As the pairs of competing fish spent more time together during a trial sequence, coho salmon began to consume more food, and brook trout began to lose more, suggesting that the results of early trials influenced fish performance later. In group trials, we hypothesized that group composition and species would not influence fish foraging success. In single species groups, coho salmon consumed more than brook trout, but the ranges overlapped. Brook trout consumption remained constant through all treatments, but coho salmon consumed more food in treatments with fewer coho salmon, suggesting that coho salmon experienced more intra- than inter-specific competition and that brook trout do not pose a substantial challenge. Based on our results, we think it is unlikely that competition from brook trout will disrupt Elwha River recolonization by coho salmon.